P086 A NOVEL CALIBRATION ALGORITHM FOR COMPARISON ACROSS PATIENT REPORTED OUTCOMES (PROS) IN VENTRAL HERNIA. (25th November 2021) - Patel, Viren; Hsu, Jesse Y.; Broach, Robyn; Christopher, Adrienne; Morris, Martin; Fischer, John
Abstract: Aim: While there are many patient-reported outcome measures (PROMs) used for ventral hernia (VH), disease-specific instruments, like the Hernia-related Quality-of-Life (QoL) Survey (HerQLes) and Abdominal Hernia-Q (AHQ), have greater accuracy in capturing broad VH-related QoL. We present a novel calibration that allows providers to convert scores between the AHQ and HerQLes, enabling unification of QoL data. Material and Methods: VH patients were prospectively identified and simultaneously administered the AHQ and HerQLes pre-and post-operatively. To ensure validity of the calibration, responses were excluded if patients answered instruments on different dates or if responses were discordant on corresponding questions on each instrument. The calibration was estimated using a linear mixed-effects model, including linear and quadratic scores, timing of survey relative to surgery and their interactions as fixed effects, and patients as random effects to account for multiple surveys from the same patient. Results: In total, 109 patients were included, responding to 300 pairs of surveys (112 pre-operative and 188 post-operative). Seventeen (5.6%) were statistically excluded due to discordant responses. Conversion of the HerQLes to AHQ was most accurate when including whether the survey was completed pre-or post-operatively, with a mean square error (MSE) of 0.0091. Similarly, converting the AHQ to HerQLes was most accurate when factoring in the timing of survey administration, with a MSE of 0.016. Conclusions: We present a novel and accurate method to convert scores between the AHQ and HerQLes. Portability of PROMs will be crucial in efforts to more broadly integrate PROMs into routine care in VH.